Waylon! : even more awesome - Pennypacker, Sara, 1951-; Frazee, Marla (2017)
"Waylon and Baxter share in the care of a stray dog, Dumpster Eddy"--
Ages 7+
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Friendship -- Fiction